Expression and secretion of glycosylated barley oxalate oxidase in Pichia pastoris. - William Donelan; ShiWu Li; Paul R Dominguez-Gutierrez; Augustus Anderson Iv; Li-Jun Yang; Cuong Nguyen; Benjamin K Canales (PLoS ONE, 2023)
Oxalate oxidase is an enzyme that degrades oxalate and is used in commercial urinary assays to measure oxalate levels. The objective of this study was to establish an enhanced expression system for secretion and purification of oxalate oxidase using Pichia pastoris. A codon optimized synthetic oxalate oxidase gene derived from Hordeum vulgare (barley) was generated and cloned into the pPICZα expression vector downstream of the N-terminal alpha factor secretion signal peptide sequence and used for expression in P. pastoris X-33 strain. A novel chimeric signal peptide consisting of the pre-OST1 sequence fused to pro-αpp8 containing several amino acid substitutions was also generated to enhance secretion. Active enzyme was purified to greater than 90% purity using Q-Sepharose anion exchange chromatography. The purified oxalate oxidase enzyme had an estimated Km value of 256μM, and activity was determined to be 10U/mg. We have developed an enhanced oxalate oxidase expression system and method for purification.